Analisis strategi penanganan pembiayaan bermasalah pada bank syariah: Studi literatur - Anggrainie, Agustina (Maliki Interdisciplinary Journal, 2024)
Providing financing by sharia financial institutions to customers is an activity that cannot be separated from the risks that the institution must face. One of the financing risks often faced by Islamic banks is problematic financing. This condition occurs when the customer cannot or will not fu lfill his obligation to repay the funds borrowed from the Islamic bank in accordance with the terms agreed in the financing agreement. This triggers Islamic banks to continue trying to deal with problematic financing by implementing effective strategies. The purpose of this research is to dig deeper into the strategies of Islamic banks in dealing with problematic financing through literature studies by previous researchers which are in accordance with the topic of discussion in this research. The research results show that the strategies implemented by sharia banks include a family approach, emphasizing sharia principles, and implementing different internal policies.